Towards a new business model for Algerian companies: The role of Mobilis Company Implementing the creating shared value approach - Guennoun, Rim (International journal of economic perspectives, 2024)
This study explores the role of Mobilis Company in implementing the Creating Shared Value (CSV) approach as a novel business model. Recognized as an innovative framework, this approach has been embraced by leading global companies across various sectors to generate mutual benefits for both businesses and society by leveraging the three key mechanisms of creating shared value. A field study was conducted using a sample of executives and managers from the company, with a questionnaire serving as the primary data collection tool. The findings indicate that Mobilis Company effectively embodies and applies the Creating Shared Value (CSV) approach, adhering to its three fundamental dimensions